COLOR MASS AND IMAGERY: VISUAL SOLUTIONS IN ALISHER NAVOI’S WORKS - Qutliyeva Mahbuba Bekpulatovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This study examines the role of color mass in Alisher Navoi’s works from the perspective of visual and artistic solutions. The research analyzes how color mass contributes to the creation of artistic imagery, compositional balance, and emotional expression, as well as its aesthetic and pedagogical significance. In Navoi’s works, color mass not only enhances artistic mood and emotional states but also serves as a tool for developing students’ visual and artistic competencies. The findings highlight both theoretical and practical aspects of working with color mass, providing insights for its application in art education.